Forward-backward box smoothing with quantized measurements - Sun Wen (Dianzi Jishu Yingyong, 2022)
In this work, we are interested in promoting tracking accuracy of target in quantized measurements by taking the de-laying measurements into consideration. Specifically, a novel forward-backward box particle smoothing algorithm is proposed. In the forward pass, the algorithm iterates with standard box particle filter. In the backward pass, smoothing posterior density is approximated by box particles. An extra moving step of box particles is proposed to concentrate the box particles around the target. Simulations under quantized measurements are presented to verify the accuracy promotion of proposed algorithm.